Fe(III)-Catalyzed diastereoselective friedel-crafts alkylation-hemiketalization-lactonization cascade for the synthesis of polycyclic bridged 2-chromanol lactones - Borade, Balasaheb R.; Nomula, Rajesh; Gonnade, Rajesh G.; Kontham, Ravindar (Organic Letters, 2019)
An unprecedented Fe(III)-catalyzed Friedel-rafts alkylation-hemiketalization-lactonization cascade of electron-rich hydroxy arenes and distinctively functionalized unsaturated 4-keto esters is developed for the construction of polycyclic bridged 2-chromanol lactones. Following this simple and facile protocol, a broad range of products was prepared in good to excellent yields as a single diastereomer. An unusual conglomerate (enantiomerically pure polymorph) of 3ac is reported along with the absolute stereochemistry, and the remaining products were rigorously confirmed by single-crystal X-ray analysis and analogy.

Total synthesis of beshanzuenone D and its epimers and abiespiroside A - Borade, Balasaheb R.; Dixit, Ruchi; Kontham, Ravindar (Organic Letters, 2020)
A unified and protecting-group-free six-step total synthesis of bisabolane-type sesquiterpenoid beshanzuenone D and its stereoisomers and abiespiroside A using S-(+)-carvone as a common chiral-pool building block is disclosed. This synthetic route features chemoselective allylic chlorination of carvone, Au(I)-catalyzed cydoisomerization induced construction of furan from homopropargylic diol, substrate-controlled selective hydroxylation using Davis-oxaziridine, and dye-sensitized photo-oxidation (through O-1(2)) of hydroxyalkyl tethered furan to access oxaspirolactone as key transformations. A comprehensive set of NMR data along with DFT calculations, ECD spectra, and optical rotation measurements of the synthesized beshanzuenone D and its epimers were obtained to confirm absolute configurations.

Bismuth(iii)-catalyzed bis-cyclization of propargylic diol-esters: a unified approach for the synthesis of [5,5]- and [6,5]-oxaspirolactones - Kambale, Digambar A.; Borade, Balasaheb R.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2021)
Herein we disclose an unprecedented intramolecular cascade strategy for the construction of alpha,beta-unsaturated [5,5]- and [6,5]-oxaspirolactones that capitalizes on the pi-electrophilic Lewis acid-catalyzed 5-exo-dig or 6-exo-dig mode of cyclization of propargylic diol esters, followed by dehydration and spirolactonization steps. Moreover, semi-protected substrates also delivered the respective oxaspirolactones with the same ease and in appreciable yields under optimal reaction conditions.

Concise total synthesis of (+)-lanceolactone a: revision of absolute stereochemistry - Borade, Balasaheb R.; Kontham, Ravindar (Journal of Organic Chemistry, 2022)
A chiral-pool protecting-group-free five-step total synthesis of tetranorsesquiterpenoide (+)-lanceolactone A and all of its four stereoisomers using (S)-(+)-, and (R)-(-)-linalool (coriandrol) as building blocks is disclosed. The key steps involved in this synthetic route are regioselective ozonolysis, Au(I)-catalyzed cycloisomerization-induced construction of furan from alleneone, and dye-sensitized photo-oxidation (through O-1(2) ; singlet oxygen) of hydroxyalkyl-tethered furan to access oxaspirolactone. After a thorough evaluation of electronic circular dichroism (ECD) and optical rotation data of all possible stereoisomers, the absolute configuration of natural lanceolactone A at the C4 and C7 positions has been assigned as (+)-(4S,7S), which is an enantiomer to the initially proposed structure (+)-(4R,7R). Further, these investigations led us to extend Feringa and Gawronski's CD correlation method to [5,5]- and [6,5]-oxaspirolactones.

Enceleamycins A-C, furo-naphthoquinones from amycolatopsis sp. MCC0218: isolation, structure elucidation, and antimicrobial activity - Khan, Abujunaid; Said, Madhukar S.; Borade, Balasaheb R.; Gonnade, Rajesh; Barvkar, Vitthal; Kontham, Ravindar; Dastager, Syed G. (Journal of Natural Products, 2022)
Three novel furo-naphthoquinones, enceleamycins A-C (1-3), and a new N-hydroxypyrazinone acid (4) were identified from the strain Amycolatopsis sp. MCC 0218, isolated from a soil sample collected from the Western Ghats of India. Their chemical structure and absolute and relative configurations were established by 1D and 2D NMR spectroscopy, single-crystal X-ray crystallography, and high-resolution mass spectrometry. Compounds 1 and 3 were active against methicillin-susceptible and -resistant Staphylococcus aureus with MIC values of 2-16 mu g/mL.

Divergent synthesis of oxepino-phthalides and [5,5]-oxaspirolactones through [2+2+2]- and [2+3]-annulation of alkynyl alcohols with a-ynone-esters - Kambale, Digambar A.; Borade, Balasaheb R.; Vinodkumar, Ramavath; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
Unmasking the synthetic potential of alkyne functional group of alkynyl alcohols as surrogates of carbonyl compounds, herein we present the first Bronsted acid (TfOH)-catalyzed [2 + 2 + 2]-annulation of 4-pentyn-1-ols (possessing terminal alkyne) with a-ynone-esters to access tricyclic tetrahydro-oxepino-phthalides. Besides, an unprecedented synthesis of a-acetoaryl or a-alkynyl [5,5]-oxaspirolactones has been demonstrated by employing 4-pentyn-1-ols (possessing an internal alkyne) as an annulation partner, which proceeds through a divergent [2 + 3]-annulation pathway.

Metabolites from lactococcus lactis subsp. lactis: isolation, structure elucidation, and antimicrobial activity - Navale, Vishwambar D.; Borade, Balasaheb R.; Rama Krishna, Gamidi; Vamkudoth, Koteswara Rao; Kontham, Ravindar (ACS Omega, 2023)
Herein, we disclose the identification of novel metabolites from a potential probiotic strain, Lactococcus lactis subsp. lactis, obtained from traditional dairy milk samples collected in Maharashtra, India (in January 2021). Isolated metabolites include pyrazin-2-carboxamide [1, pyrazinamide, a potential antitubercular drug], 3,5-dihydroxy-6-methyl-2,3-dihydro-4H-pyran-4-one (2, DDMP), 2,4-di-tert-butylphenol (3), and hexadecanoic acid (4, palmitic acid). The chemical structures of these metabolites were elucidated through extensive 1D NMR (H-1 and C-13) and 2D NMR (HSQC, HMBC, and NOESY) analyses, high-resolution mass spectrometry, high-performance liquid chromatography, and single-crystal X-ray crystallography. Furthermore, these novel metabolites exhibited potent inhibitory activities against various bacteria, fungi, and yeast strains with minimum inhibitory concentrations ranging between 1.56 and 25 mu g/mL, and compounds 1 and 3 were found to be most active against a wide range of microbial strains tested.

Bi(OTf)3-promoted cascade annulation of hydroxy-pyranones and unsaturated γ-ketoesters for the construction of polycyclic bridged pyrano-furopyranones - Rathod, Akshay B.; Borade, Balasaheb R.; Sambherao, Pooja I.; Kontham, Ravindar (Organic and biomolecular chemistry, 2024)
An efficient protocol for constructing complex three dimensional polycyclic bridged chromano-furopyranones and pyrano-furopyranones (closely related to bioactive natural products) via bismuth(III)-catalyzed cascade annulation of hydroxy-pyranones and unsaturated gamma-ketoesters is presented. This process involves intermolecular Michael addition, intramolecular hemiketalization, lactonization, formation of one C-C bond and two C-O bonds, rings, and contiguous stereocenters.
Keywords: 1 3-Dicarbonyl Compounds; alkynols; Coumarins; Fungus

Divergent access to α-carbonyl-α′-vinyl sulfoxonium ylides and polysubstituted furans from β-ketosulfoxonium ylides and ynone-esters - Ingale, Sudhir R.; Sahu, Manas Ranjan; Borade, Balasaheb R.; Gamidi, Rama Krishna; Kontham, Ravindar (Journal of Organic Chemistry, 2025)
Here, we describe the synthesis of novel alpha-carbonyl-alpha `-vinyl sulfoxonium ylides under ambient, catalyst-free, and additive-free conditions, demonstrating broad substrate scope and scalability using beta-ketosulfoxonium ylides and alpha-ynone-esters. Furthermore, these ylides serve as versatile intermediates for the synthesis of highly substituted furans via Br & oslash;nsted acid (p-TsOH) catalysis at 130 degrees C. This approach offers key advantages, including wide substrate compatibility, divergent product formation from common precursors, gram-scale feasibility, and good to excellent yields.